Virtual Animated Media with Local Wisdom for Learning to Read using Mind Method - Samsiyah, Nur; Suharto, V. Teguh; Ulya, Chafit (Universitas Muhammadiyah Malang, 2024)
The objectives of the research are to: 1) explain the conditions of class 4 elementary schools in Madiun City; 2) describe and explain the model for developing virtual animation media containing local wisdom for learning to read for grade 4 students; 3) describe and explain the effectiveness of virtual animation media products containing local wisdom for learning to read through the Mind Mapping method for grade 4 elementary school students. This type of development research useD the simplified Borg and Gall method in 4 stages: exploration, design development, testing, and deployment. Data analysis was done using descriptive analysis, feasibility tests with criteria scores, and reading comprehension tests with t-tests. Results of the research were: 1) students still use thematic book media. Learning to read was still a task of answering questions. 2) the needs and characteristics of learning media were summarized as follows, (a) attractive animated media according to basic competencies in the curriculum, with local wisdom content (b) easy to use, (c) equipped with evaluations to measure students' reading comprehension. 3) the test results were categorized as good and feasible. (4) Media effectiveness showed a value of 0.29 greater than 0.05. The homogeneity test at the extensive test stage received a value of 0.109 which indicated significance, and the normality test with a value of 0.622 which means the population had homogeneous variance. The results of the Tukey test showed differences between the experimental and control groups. Virtual animation media is effective in reading comprehension through the mind mapping method for grade 4 students.